2012
DOI: 10.1007/s00726-012-1425-5
|View full text |Cite
|
Sign up to set email alerts
|

Vaspin attenuates the apoptosis of human osteoblasts through ERK signaling pathway

Abstract: It has been hypothesized that adipocytokines originating from adipose tissue may have an important role in bone metabolism. Vaspin is a novel adipocytokine isolated from visceral white adipose tissue, which has been reported to have anti-apoptotic effects in vascular endothelial cells. However, to the best of our knowledge there is no information regarding the effects of vaspin on osteoblast apoptosis. This study therefore examined the possible effects of vaspin on apoptosis in human osteoblasts (hOBs). Our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 42 publications
4
45
1
2
Order By: Relevance
“…The researches about vaspin were mainly focused on the insulin resistance [77], hepatitis disease [78, 79], and cardiovascular disease [80, 81]. Presently, our previous study showed that the vaspin could inhibit the apoptosis of the osteoblasts [82]. However, no report about its function in osteogenesis, osteoclastogenesis as well as the relation with BMD was published.…”
Section: Adipokines and Bone Metabolismmentioning
confidence: 99%
“…The researches about vaspin were mainly focused on the insulin resistance [77], hepatitis disease [78, 79], and cardiovascular disease [80, 81]. Presently, our previous study showed that the vaspin could inhibit the apoptosis of the osteoblasts [82]. However, no report about its function in osteogenesis, osteoclastogenesis as well as the relation with BMD was published.…”
Section: Adipokines and Bone Metabolismmentioning
confidence: 99%
“…Vaspin was strongly expressed at the peak of obesity and insulin resistance (Hida et al 2005). It was recently reported that vaspin inhibited serum deprivationinduced apoptosis in human osteoblasts (Zhu et al 2013). Thus, it is considered that vaspin may be involved in pathogenesis of metabolic disorders including obesity and diabetes as well as bone metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Hence the final conclusion that vaspin downregulates osteoclastogenesis in part by inhibiting expression of the transcription factor NFATc1 [28]. Vaspin also attenuated the apoptosis of human osteoblasts [29]. Western blot analysis indicates that, depending on the dose, vaspin upregulates the expression of anti-apoptotic gene Bcl-2 and downregulates the expression of BAX, which plays a crucial role in apoptosis induction.…”
Section: Prace Oryginalnementioning
confidence: 94%
“…Kamio et al [28] concluded that vaspin inhibited RANKL-induced osteoclastogenesis in RAW264.7 cells and bone marrow cells. It also attenuated the apoptosis of human osteoblasts [29]. Hence the hypothesis that changes in vaspin levels observed in girls with AN [22] might play a role in inducing changes in bone metabolism found in these patients, the effect of which might be mediated by the RANKL/RANK/OPG system.…”
Section: Introductionmentioning
confidence: 99%